Establishing the most favorable metal–carbon bond strength for carbon nanotube catalysts. Issue 14 (14th April 2015) - Silvearv, Fredrik; Larsson, Peter; Jones, Sarah. L. T.; Ahuja, Rajeev; Larsson, J. Andreas
<x xml:space="preserve">Abstract</x> We have studied a wide range of transition metals to find potential carbon nanotube (CNT) catalysts for chemical vapor deposition (CVD) production.